2022
DOI: 10.1007/s40801-022-00296-5
|View full text |Cite
|
Sign up to set email alerts
|

Context and Considerations for Use of Two Japanese Real-World Databases in Japan: Medical Data Vision and Japanese Medical Data Center

Abstract: In Japan, an increasing interest in real-world evidence for hypothesis generation and decision-making has emerged in order to overcome limitations and restrictions of clinical trials. We sought to characterize the context and concrete considerations of when to use Medical Data Vision (MDV) and JMDC databases, the main Japanese real-world data (RWD) sources accessible by pharmaceutical companies. Use cases for these databases, and related issues and considerations, were identified and summarized based on a lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…After screening the titles and abstracts, 632 studies (NDB, 40 studies; JMDC, 185 studies; MDV, 147 studies; and DPC, 260 studies) were included in this review. A total of 28 studies were added from a previous review of the NDB [ 7 ] and seven from a manual search. Of these, 14 studies were counted as duplicates because they used both the JMDC and MDV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the titles and abstracts, 632 studies (NDB, 40 studies; JMDC, 185 studies; MDV, 147 studies; and DPC, 260 studies) were included in this review. A total of 28 studies were added from a previous review of the NDB [ 7 ] and seven from a manual search. Of these, 14 studies were counted as duplicates because they used both the JMDC and MDV.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to understand the characteristics of each database to select the most appropriate database for each research study. The characteristics of each database and aspects to consider when conducting research have already been reported [ 3 , 7 ], but it is not clear whether the research conducted in each database corresponds to the features already pointed out. The only study that has examined the types of studies conducted in the Japanese administrative claims databases was for the NDB [ 8 ], and there have been no studies that have compared the types and designs of studies conducted in each database.…”
Section: Introductionmentioning
confidence: 99%
“…The MDV database provides a large representative sample of anonymized Japanese patient data, medical costs, and laboratory results. 7 Additionally, information regarding clinical evaluation of AHP and its types is limited in the literature. This study provides a clinical description of patients who are experiencing several types of porphyria across multiple medical specialties and/or departments, which may assist physicians in recognizing these cases earlier in the disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…We used the nationwide health insurance claims database obtained from the medical database vendor JMDC Co., Ltd (Tokyo, Japan) 24 . This database collects anonymized inpatient, outpatient, and dispensing claims data from various health insurance associations and has accumulated over 10 million people since 2005 (approximately 10% of the Japanese population) 25 . As this database is sourced from health insurance associations for company employees and their families, it is representative of the relatively young generation, which is advantageous for maternal health care research 26 , 27 .…”
Section: Methodsmentioning
confidence: 99%